Factor of political support in N27 Sebuyau Sarawak Barisan Nasional / Monalissa Mariah Brain and Yusra Syazwani Muas - Brain, Monalissa Mariah; Muas, Yusra Syazwani (2016)
This research study is about the factor of political support in N27 Sebuyau Sarawak Barisan Nasional. We want to identify the factors and reason of the Sarawak Barisan Nasional victory and why does the voters in Sebuyau still support Sarawak Barisan Nasional even though there are lot of negative issues of Sarawak Barisan Nasional. The result of this research are most of the people who support Sarawak Barisan Nasional in Sebuyau area is because of the their representative, the contribution from Sarawak Barisan Nasional and also for the sake ofthe government which they don’ want to be lead by other parties. However, we can see that not all the villagers in Sebuya support Sarawak Barisan Nasional.